Pedagogical Debates on Educational Innovation - Dopico, Eduardo (American Journal of Education and Learning, 2020)
Educative innovation is a constant dynamic in the process of improving the educational system. Responding to criteria of need, opportunity, coherence and replicability, the introduction of changes, modifications in the academic guidelines contributes to the progress of teaching and the quality of education. Initial and continuous teacher training is an essential part of the innovative initiatives. Throughout four pedagogical workshops related to teaching practice, 181 teachers of Secondary Education opened, a dynamic of debates to stimulate critical reflection and the exchange of information and ideas about innovation of pedagogical work. The teachers shared their interests and concerns about the tasks of innovating in the classroom and introducing improvements in the school organization itself. Results indicated that barriers to innovation are still embedded in school routines, and highlighted also the advantages of innovation for the participants. This study points out to the need to stimulate changes in the school organization and encourage teachers to facilitate the implementation of innovative proposals.